FERMENTASI TEPUNG BULU AYAM DENGAN Bacillus licheniformis B2560 UNTUK MENINGKATKAN KUALITAS BAHAN BAKU PAKANIKAN - Dini Siswani Mulia; Yesi Nartanti; Heri Maryanto; Cahyono Purbomartono (Universitas Sebelas Maret, 2014)
Abstract - The purpose of this study is to examine fermentation of chicken feather meal with Bacillus licheniformis B2560 to improve the quality of fish feed ingredients. The study was conducted using an experimental method to completely randomized design (CRD) 4 treatments, 3 replications, ie P0 = non- fermented ; P1 = 5 ml inoculum fermentation with B. licheniformis B2560 ; P2 = 10 ml inoculum fermentation with B. licheniformis B2560 ; and P3 = 15 ml inoculum fermentation with B. licheniformis B2560, respectively for chicken feather meal as much as 2 g .Parameters measured were the levels of protein and organoleptic parameters that support, in the form of the physical properties of chicken feather meal, include color, texture, and smell. Data were analyzed using a protein content analysis of variance (ANOVA) with a confidence level of 95 %, followed by Duncans Multiple Range Test Test (DMRT) with a confidence level of 95 % , while for the data results of the organoleptic qualitatively analyzed descriptively.The results showed that the P0 treatment was significantly different (P < 0.05) with P1, P2, and P3, and between treatments P1, P2, and P3 respectively were significantly different (P < 0.05). The treatment gives the best results is the treatment that P1 has the highest protein content of 84.08 % with a change in the physical properties of white -yellow (color), soft (texture), and less typical sting (smell). Keywords :Bacillus licheniformis B2560, fermentation, the quality of raw materials, chicken feather meal, Fish feed